2002
DOI: 10.1097/00003226-200203000-00001
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Efficacy of Silicone Punctal Plug Therapy

Abstract: Punctal plug insertion is a simple, effective, safe, and reversible method to treat aqueous tear deficiency and other ocular surface diseases, such as epitheliopathy after penetrating keratoplasty, superior limbic keratoconjunctivitis, neurotrophic keratitis, recurrent corneal erosions, and toxic epitheliopathy not controlled by lubrication with preservative-free tears. However, spontaneous extrusion of silicone plug occurs commonly. Careful choosing of the optimal plug size and close follow-up are recommended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(84 citation statements)
references
References 16 publications
2
78
0
4
Order By: Relevance
“…The function of the lens is to provide a fluid cushion for the cornea and protect it from the rubbing effects of the lids [38,39,40]. Some authors have noticed an improvement in the cornea through the use of temporary silicone plugs to help increase tear volume [41]. …”
Section: Treatmentmentioning
confidence: 99%
“…The function of the lens is to provide a fluid cushion for the cornea and protect it from the rubbing effects of the lids [38,39,40]. Some authors have noticed an improvement in the cornea through the use of temporary silicone plugs to help increase tear volume [41]. …”
Section: Treatmentmentioning
confidence: 99%
“…Consistent with our results, previous studies have shown that spontaneous plug loss is the most common problem with punctal plugs, occurring in 30 --50%. 9,10 Other known possible complications of punctal occlusion include pruritus, discomfort, lesions of the conjunctiva and cornea, epiphora, canaliculitis and pyogenic granuloma. 11 None of the aforementioned was observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A oclusão do ponto lacrimal ajuda a reter, na superfície ocular, tanto a lágrima natural quanto as lágrimas artificiais, bloqueando a sua drenagem (18) . Esta oclusão pode (19)(20) . Os plugs são utilizados com maior freqüência pelo fato de ser um procedimento ambulatorial e reversível.…”
Section: Discussionunclassified